Analisis strategi pada pembiayaan bank syariah dalam meningkatan usaha pertanian - Difri, Fanesa Ainun (Maliki Interdisciplinary Journal, 2024)
This article discusses how sharia banks can play a role in improving agricultural businesses in Indonesia through financing strategies that comply with sharia principles. Even though the agricultural sector has a large contribution to the economy, this sector faces problems such as lack of capital and low productivity. Through a literature review approach, this research examines the effectiveness of financing sharia products such as muzara’ah and bai salam in improving farmers’ welfare. However, challenges such as a lack of understanding of sharia products and stigma against agriculture still exist. Therefore, this article emphasizes the need for cooperation between Islamic banks and farmers, as well as educational programs to increase awareness of financing products. Suggestions include increased promotion, cost transparency, and collaboration with the government to support agricultural infrastructure.